(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
Planning is a significant process function and counterpoises a very complex, dynamic and specific activity, which means that its subject consists of all forms of social activity, activities and life. Planning and programming are equally important to all entities regardless of their size and goals, as they all have experienced painful problems with their planning efforts. Some emerge from the planning process itself, and some from the implementing procedure. Therefore the question arises: „How to help overcome failures in planning from failures in implementation?” Hence, the management team has no choice regarding the question: “Do they want to plan or not?” The sole alternative is to carry out the planning completely, pragmatically and systematically. On the other hand, programming connects planning with budgeting and execution, and counterpoises a sort of rational assumption to “turn” plans from adopted plans into programs, that is, projects and activities across main accounting categories, in accordance with the desired capabilities and priorities. The analysis of the entire matter processed in this paper is carried out in a very specific way through the prism of identifying not only the problems related to planning, programming and budgeting, but also making a scientific contribution to the foundation of this rather significant conditionality and interdependence.